Jual Beli Saham: (Suatu Kajian Praktek Jual Beli Online Shopee) - Zulhamdi, Zulhamdi (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2022)
Buying and selling with a salam contract is a buying and selling with an order system, which means that the delivery of goods is not directly at the time of order but is delayed at a particular time which has been agreed by both parties. In buying and selling with a salam contract, the payment system is carried out before the goods are delivered, for example in online buying and selling transactions on the Shopee application using the internet media. Shopee is online buying and selling media based on mobile application which is currently developing in Indonesia. Buyers take advantage of the online shop media to have the desired items easily without having to leave the house. This study which used a qualitative method aimed to determine the relevance of the implementation of online buying and selling on Shopee services with the implementation of buying and selling with a salam contract.